Análise de técnicas de normalização aplicadas ao reconhecimento facial - Andrezza, Igor Lucena Peixoto (2015)
Biometrics offers a reliable authentication mechanism that identifies the users through their physical and behavioral characteristics. The problem of face recognition is not trivial because there are many factors that affect the face detection and recognition, as for example, lighting, face position, hair, beard, etc. This work proposes to analyze the effects of geometric and lighting normalization on face recognition techniques, aiming to adapt them to uncontrolled environments. The results show that the utilization of background information in the normalization process increases the face recognition error rates and this happens in many papers in the literature. The lighting and geometric normalization methods, when performed with precise points of the eyes centers, effectively help in face recognition.